2008
DOI: 10.2337/db07-1241
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of RhoA/ROCK Signaling Ameliorates Progression of Diabetic Nephropathy Independent of Glucose Control

Abstract: OBJECTIVE-RhoA, a small GTPase protein, and its immediate downstream target, Rho kinase (ROCK), control a wide variety of signal transduction pathways. Recent studies have shown that fasudil, a selective ROCK inhibitor, may play a pivotal role in a number of pathological conditions, ranging from cardiovascular diseases to pulmonary hypertension and erectile dysfunction. Considerable evidence suggests that some of the beneficial effects of statins may also stem from their modulatory effects on RhoA/ROCK signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
169
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 53 publications
14
169
3
Order By: Relevance
“…Our data indicated that fasudil may improve the enhanced GFR during the very early stage of nephropathy. No difference in serum creatinine or creatinine clearance was observed between groups at month 3 or 8, which agrees with previous studies [5,27] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data indicated that fasudil may improve the enhanced GFR during the very early stage of nephropathy. No difference in serum creatinine or creatinine clearance was observed between groups at month 3 or 8, which agrees with previous studies [5,27] .…”
Section: Discussionsupporting
confidence: 82%
“…Further studies are required to determine whether fasudil has specific role in the control of blood pressure. Low-dose (10 mg/kg) fasudil had no effect in this study, which is different from previous studies [4,27] , and may be related to the differences in animal models, treatment periods and protocols.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that ROCK can directly activate JNK to stimulate c-Jun expression, the activity of which is independent of the ability of ROCK to promote actin polymerization [40] . Fasudil (10-30 mg·kg -1 ·d -1 ) can suppress renal interstitial fibrosis in insulin-resistant diabetic rats [7,8] . ROCK inhibition also improves pressure overload-induced cardiac hypertrophy and dysfunction [41] .…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that RhoA/ROCK signaling mediates the glomerular matrix accumulation of proteins in diabetic nephropathy. The ROCK inhibitor fasudil can suppress renal fibrosis and can reduce proteinuria [7,8] . The inhibition of ROCK attenuates cardiac fibrosis in angiotensin II-induced cardiac hypertrophy in vivo [9,10] .…”
Section: Introductionmentioning
confidence: 99%